ЛІНГВОПРАГМАТИЧНИЙ ПОТЕНЦІАЛ ІЛЮСТРАТИВ-НО-ВІЗУАЛЬНИХ ЗАСОБІВ У НОВИННОМУ ДИСКУРСІ BBC ТА CNN - ГЕТМАН, Вікторія (Мовні і концептуальні картини світу, 2024)
Статтю присвячено аналізу функціонування візуально-зображальних елементів у текстах новин міжнародних корпорацій ВВС та CNN. Серед усього спектру таких елементів фотографії та ілюстрації використовуються найчастіше з огляду на функціональне призначення новинного дискурсу. Було визначено, що на онлайн сторінках новин ВВС та CNN світлини виконують такі комунікативні функції, як засвідчування подій на підтвердження істинності фактів; унаочнення та демонстрація явищ, сенсацій, життєвих ситуацій; привернення уваги потенційних читачів. Як персуазивний елемент, фотографії використовують з метою емотивного, пізнавально-роз’яснювального та пізнавально-естетичного впливу на реципієнтів. Щодо характеру взаємовідносин між фотографією та текстом до неї, то фото і текст можуть бути повністю незалежним один від одного чи перебувати у взаєминах компліментарності, або бути залежними та перебувати на одному рівні узагальнення чи містити деталізуючі компоненти. ____________СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛArnheim, R. (2004). Art and Visual Perception: A Psychology of the Creative Eye. University of California Press.Bateman, J. (2014). Text and Image: A Critical Introduction to the Visual/Verbal Divide. New York.Bednarek, M., Caple, H. (2017). The Discourse of News Values: How News Organizations Create Newsworthiness. Oxford University Press.Kovalenko, L., & Martynyuk, A. (2021). Verbal, visual, and verbal-visual puns in translation: cognitive multimodal analysis. Cognition, communication, discourse, 27-41.Kress, G., & Leeuwen, T. van. (2020). Reading Images: The Grammar of Visual Design. Routledge, 3rd edition.Leeuwen, van Theo. (2004). The reasons why linguists should pay attention to visual communication. Discourse and technology: multimodal discourse analysis. Georgetown University round table on languages and linguistics series, 7–20.Lester, P.M. (2013). Visual Communication: Images with Messages. Wadsworth Publishing, 6th edition.Maldonado, R. (2023). Increasing Visual Literacy and Critical Thinking Skills through Graphic Novels. Rowman & Littlefield Publishers.Martinec, R., & Salway, A. (2005). A system for image-text relations in new (and old) media. Visual communication, 4(3), 337–371.Newman, M., & Ogle, D. (2019). Visual Literacy: Reading, Thinking, and Communicating with Visuals. Rowman & Littlefield Publishers.Page, J. T., & Duffy, M. (2021). Visual Communication: Insights and Strategies. Wiley-Blackwell.Painter, C., & Martin, J., & Unsworth, L. (2012). Reading visual narratives: Image analysis in children’s picturebooks. UK: Equinox Publishing Ltd.Royce, T. (2010). Linking the Visual and the Verbal: Developing multimodal academic literacy. Conference Selections, 1–55.Serafini, F. (2020). Understanding visual images in picture books . Talking beyond the page. Routledge, 10–25.Tsapiv, A. (2022). Multimodal imagery in picture books for children. Cognition, communication, discourse, 25, 80-88.Wignell, P., & O’Halloran, K. L., & Tan, S., & Lange, R., & Chai, K. (2018). Image and text relations in ISIS materials and the new relations established through recontextualisation in online media. Discourse & Communication, 12(5), 535–559.Wildfeuer J. (2012). More than WORDS. Semantic Continuity in Moving Images. Online Magazine of the Visual Narrative, 13(4), 181–203.Yefymenko V. (2022). Multimodality and cross-modal cohesion in manga. Cognition, communication, discourse, 103–114. ДЖЕРЕЛА ІЛЮСТРАТИВНОГО МАТЕРІАЛУJewish fears as German support for Israel is challenged on streets - BBC News. https://www.bbc.com/news/world-europe-67368409US veteran gets world's first eye transplant - BBC News. https://www.google.com/search?q=US+veteran+gets+world%27s+first+eye+transplant+-+BBC+News&oq=US+veteran+gets+world%27s+first+eye+transplant+-+BBC+News+&gs_lcrp=EgZjaHJvbWUyBggAEEUYOTIKCAEQABiABBiiBDIKCAIQABiABBiiBDIKCAMQABiABBiiBDIKCAQQABiABBiiBDIKCAUQABiABBiiBNIBCTM2ODBqMGoxNagCCLACAQ&sourceid=chrome&ie=UTF-8 Pakistan’s Lahore is the latest megacity to shut down as pollution chokes swathes of South Asia | CNN. https://www.google.com/search?q=Pakistan%E2%80%99s+Lahore+is+the+latest+megacity+to+shut+down+as+pollution+chokes+swathes+of+South+Asia+%7C+CNN&oq=Pakistan%E2%80%99s+Lahore+is+the+latest+megacity+to+shut+down+as+pollution+chokes+swathes+of+South+Asia+%7C+CNN&gs_lcrp=EgZjaHJvbWUyBggAEEUYOdIBCTI3NDBqMGoxNagCCLACAQ&sourceid=chrome&ie=UTF-8 Russia has tried to break Ukraine’s energy grid. This winter, Ukrainians are prepared for the worst | CNN. https://www.google.com/search?q=Russia+has+tried+to+break+Ukraine%E2%80%99s+energy+grid.+This+winter%2C+Ukraini-ans+are+prepared+for+the+worst+%7C+CNN&oq=Russia+has+tried+to+break+Ukraine%E2%80%99s+energy+grid.+This+winter%2C+Ukraini-ans+are+prepared+for+the+worst+%7C+CNN+&gs_lcrp=EgZjaHJvbWUyBggAEEUYOdIBCTI4NjdqMGoxNagCCLACAQ&sourceid=chrome&ie=UTF-8 Live updates: Israel-Hamas war, raid on Al-Shifa hospital in Gaza. cnn.com.Ukraine war: Russian artist Sasha Skochilenko jailed for anti-war messages - BBC News. https://www.bbc.com/news/world-europe-67437171Ukraine claims a new ‘foothold’ in the country’s south. What does that mean for Kyiv’s efforts to keep the West on its side? | CNN. https://edition.cnn.com/2023/11/16/europe/ukraine-war-dnipro-russia-intl/index.html How return-to-office uncertainty is leaving workers in limbo - BBC Worklife. https://www.bbc.com/worklife/article/20220719-how-return-to-office-uncertainty-is-leaving-workers-in-limboBoom Supersonic unveils new design for Overture supersonic jet | CNN. https://edition.cnn.com/travel/article/boom-supersonic-unveils-new-design-for-overture/index.htmlFossil of largest Jurassic pterosaur found on Skye - BBC News. https://www.bbc.com/news/science-environment-60407928Winslow Homer: A chronicler of US turbulence - BBC Culture. https://www.bbc.com/culture/article/20220719-winslow-homer-a-chronicler-of-us-turbulenceChina and Taiwan: A really simple guide - BBC News. https://www.bbc.com/news/world-asia-china-59900139Forced to wait by the judge, Trump is out of his comfort zone - BBC News. https://www.bbc.com/news/world-us-canada-66399284Photographer captures 'face' in breaking wave at Roker - BBC News. https://www.bbc.com/news/uk-england-tyne-64797807Dusky tetraka: Joy as bird feared extinct spotted in Madagascar - BBC News. https://www.bbc.com/news/world-africa-64822787How ancient 'skywells' are keeping Chinese homes cool - BBC Future. https://blog.adafruit.com/2023/07/22/how-ancient-skywells-are-keeping-chinese-homes-cool/Months of planning and days of secrecy led to Joe Biden's historic trip to Kyiv | CNN Politics. https://edition.cnn.com/2023/02/20/politics/president-biden-kyiv-trip/index.htmlTyphoon Doksuri and Khanun: Thousands in China flee homes as one soaks Beijing and the second approaches | CNN. https://edition.cnn.com/2023/07/31/asia/china-beijing-typhoon-doksuri-khanun-damage-intl-hnk/index.htmlThe live volcano sitting below Santorini | CNN. edition.cnn.comTina Turner: 10 simply the best songs and the stories behind them - BBC News. https://www.bbc.com/news/entertainment-arts-65672639 'Energy vampires' lurk at work. Protect yourself with these tips | CNN. https://edition.cnn.com/2022/03/24/health/energy-vampire-in-person-work-wellness/index.html
Keywords: онлайн новини, ілюстративно-візуальні компоненти, комунікативні функції, взаємозв’язок між текстом та фото